APPLICATIONS INTRODUCTION TO THE SOLAR SYSTEM USING MACROMEDIA FLASH MX - Rizky Kurniawan; Ire Puspa Wardhana, SKom, MMSI (Jurnal Sistem Informasi, 2006)
This writing disc usses about the solar system and its contents. This application made its appearance more interesting than the book.  With this application users can learn more about the solar system  knowledge and its contents so that users can grow and get to know bendaben da sky contained in the solar system.  This paper described the design phase until the application  begins. The expectation is that applications can be made as desired  and structured.